Poetry in English : (Oxford Univ. Press, 1987)
This authoritative, handsomely designed anthology of poetry from the Anglo-Saxon to the contemporary stresses major figures without neglecting minor ones of quality. Meant for survey and genre courses (and for all interested readers), it offers responsible scholarly texts for study in themselves and for seeing both the continuities and the changes in dominant modes over the centuries. The larger aim is to enhance the appreciation of poetic art generally.